Intention to Use Mobile Learning in Higher Education Institutions: Review Paper - Izkair, Ayad Shihan; Lakulu, Muhammad Modi; Mussa, Ibtihal Hassan (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2020)
Mobile learning is presently taking part in associate degree more and more important role within the instructional method, additionally as within the development of teaching and learning ways for higher education. The power to find out ‘on the go– anytime, anywhere, is changing into more and more fashionable. The advantages offered by mobile learning are important. On the opposite hand, the implementation of mobile learning in educational activity relies on users’ acceptance of technology. Acceptance and intention to use mobile learning may be a topic of growing interest within the field of education. The model of the unified theory of acceptance and use of technology (UTAUT) is planned and developed by researchers via a mixture of eight major theories in activity prediction. UTAUT is among the foremost fashionable and up to date model in information technology acceptance. This is review paper aiming to review UTAUT’s previous studies of intention to use mobile learning. In conclusion, this research provides insight regarding the necessary factors for planning and designing an intention to use mobile learning model in higher education institutions.